Proceedings of the 3rd Brazilian Technology Symposium Emerging Trends and Challenges in Technology - Iano, Yuzo; Arthur, Rangel; Saotome, Osamu; Vieira Estrela, Vania; Loschi, Hermes José (Springer International Publishing : Imprint: Springer, 2019)
This book presents the proceedings of the 3rd Brazilian Technology Symposium (BTSym), which is a multi/trans/interdisciplinary event offering an excellent forum for presentations and discussions of the latest scientific and technological developments in various areas of research, with an emphasis on smart design and future technologies. It brings together researchers, students and professionals from the industrial and academic sectors to discuss current technological issues. Among the main topics covered in this book, we can highlight Artificial Neural Networks, Computational Vision, Security Applications, Web Tool, Cloud Environment, Network Functions Virtualization, Software-Defined Networks, IoT, Residential Automation, Data Acquisition, Industry 4.0, Cyber-Physical Systems, Digital Image Processing, Infrared Images, Patters Recognition, Digital Video Processing, Precoding, Embedded Systems, Machine Learning, Remote Sensing, Wireless Sensor Network, Heterogeneous Networks, Unmanned Ground Vehicle, Unmanned Aerial System, Security, Surveillance, Traffic Analysis, Digital Television, 5G, Image Filter, Partial Differential Equation, Smoothing Filters, Voltage Controlled Ring Oscillator, Difference Amplifier, Photocatalysis, Photodegradation, Cosmic Radiation Effects, Radiation Hardening Techniques, Surface Electromyography, Sickle cell disease methodology, MicroRNAs, Image Processing Venipuncture, Cognitive Ergonomics, Ecosystem services, Environmental, Power Generation, Ecosystem services valuation, Solid Waste and University Extension.